A Review on Xenobiotics: The Impact of SARS-CoV-2 on the Evolutionary Development of Human - Vladyko, A.; Fomina, E.; Semizhon, P. (Issues and Development in Health Research Vol. 6, 2021)
There are many assumptions about the timing of the finish of the COVID-19 coronavirus pandemic. The experience of the development of previously identified coronavirus epidemics in 2002 (SARS) and 2012 (MERS) indicates a 1-2-year duration. However, there are still many questions related to the course of past epidemics and this pandemic. It is known from the literature data that the mortality rate, for example, during the 2002 SARS epidemic, it was about 10%, in MERS – 35%, while in SARS-CoV-2 it is approximately 3-4%. Then why is the SARS-CoV-2 infection declared a pandemic, and SARS 2002 an epidemic? It is still unclear why the vaccine does not reduce the course of the coronavirus pandemic? And can any vaccine developed by traditional technology aimed at neutralizing the pathogen and stopping its circulation in the human population, prevent the spread of the infectious agent? What is the cause or source of the infection? Why are there no vaccines against human immunodeficiency virus and hepatitis C? Why are the biological characteristics of each person ignored during vaccination? When will the SARS-CoV-2 mutations stop? What role does the environment play in the development of the pandemic? Maybe the COVID-19 coronavirus pandemic did not begin in December 2019, but with the appearance of mammals on earth? Who or what is the regulator of the evolution of all living things on the planet? This message attempts to answer all the questions raised.